Ignition Different Mode of Corona Discharge in Air at Atmospheric Pressure; Energy Fluxes and Radiation Effects (EFRE-2020 online) - Tarasenko V. F. Victor Fedotovich; Kuznetsov V. Vladimir; Skakun V. Viktor; Baksht E. Evgeniy; Panarin V. Viktor; Sosnin E. Edward (2020, 2020)
Title screen